The characteristic, diagnosis and treatment of neuroendocrine gastrointerstinal tract tumors - Kunkel, Marta (Przewodnik Lekarza/Guide for GPs, 2005)
Neuroendocrine tumors are the group of specific neoplasms originated from APUD cells, in gastrointestinal tract they are rather casual patology – 2% of all gastrointestinal tumors. In spite of histological similary, the clinical symptoms are quite different, and dependent on hypersecretion of one particular hormone, which gives the name for the tumor. The main brake through in the diagnostic process and therapy of those tumors was the introduction of somatostatin analogs.